Cyclodextrin Applications in Medicine, Food, Environment and Liquid Crystals (Environmental Chemistry for a Sustainable World, 2018)
This book is the second volume of two volumes on cyclodextrins published in the series Environmental Chemistry for a Sustainable World. This volume focuses on cyclodextrin applications. The first chapter by Divya Arora and Sundeep Jaglan presents cyclodextrin-based carriers for delivery of dietary phytochemicals. The second chapter by Éva Fenyvesi et al. describes the interactions of steroids with cyclodextrins and their applications to pharmaceuticals, food, biotechnology and environment. Nazli Erdoğar and Erem Bilensoy discuss cyclodextrin-based nanosystems in targeted cancer therapy. Miriana Kfoury et al. review the use of cyclodextrins for essential oils applications in chapter 4. Hiroshi Ikeda demonstrates in chapter 5 that chromophore-appended cyclodextrins are effective for chemosensors to detect organic molecules by fluorescence or absorbance changes. Then Grégorio Crini et al. describe silica materials-containing cyclodextrin for pollutant removal. The final chapter by Chang-Chun Ling et al. summarizes the synthesis and characterization of supramolecular liquid crystals based on cyclodextrins and their applications.